Hypofractionated Radiotherapy in Head and Neck Cancer Elderly Patients: A Feasibility and Safety Systematic Review for the Clinician - Piras, Antonio; Boldrini, Luca; Menna, Sebastiano; Venuti, Valeria; Pernice, Gianfranco; Franzese, Ciro; Angileri, Tommaso; Daidone, Antonino (Frontiers in Oncology, 2021)
Objective Radiotherapy (RT) in the head and neck (H&N) site are undoubtedly the most challenging treatments for patients. Older and frail patients are not always able to tolerate it, and there are still no clear guidelines on the type of treatments to be preferred for them. The recommendations for Risk-Adapted H&N Cancer Radiation Therapy during the coronavirus disease 2019 (COVID-19) pandemic provided by the ASTRO-ESTRO consensus statement achieved a strong agreement about hypofractionated RT (HFRT). A systematic literature review was conducted in order to evaluate the feasibility and safety of HFRT for older patients affected by H&N malignancies. Materials and Methods A systematic database search was performed on PubMed and Embase according to Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA) guidelines. Original studies, case series, and case reports describing the use of HFRT (with at least 2.2 Gy fractions) in patients with mean age ≥65 years were included. The analysis was based on the type of study, number of patients, mean age, tumor site, histology, performance status (PS), RT details, concomitant chemotherapy (CT), and described clinical outcomes. All the reported doses have been calculated in equivalent dose in 2 Gy fractions (EQD2) and biologically effective dose (BED) using α/β = 10 Gy or α/β = 12 Gy. Results We selected 17 papers that met the inclusion criteria and divided them in 4 categories: 6 articles analyze HFRT performed twice daily in repeated cycles, 3 once a day in repeated cycles, 4 in alternative days, and the last 4 in consecutive days. Conclusion HFRT seems to be a good treatment with an acceptable prolonged disease control. In older patients fit for radical treatments, a 55 Gy in 20 fractions regimen can be proposed as a valid alternative to the standard fractionated RT, but there are a multitude of hypofractionated regimens, ranging from single fraction, quad shot, and 1-, 2-, 3-, 4-, and 5-week schedules that all may be appropriate. The correct regimen for a patient depends on many factors, and it represents the result of a more specific and complex decision.